2021
DOI: 10.3390/ijms22073641
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 as a Potential Therapeutic Target for Periodontitis and Its Inhibition by Caffeic Acid Phenethyl Ester In Vitro

Abstract: Salivary levels of interleukin-8 (IL-8) are elevated in patients with periodontitis. Caffeic acid phenethyl ester (CAPE) improves the periodontal status in subjects. However, whether CAPE can reduce IL-8 expression is unclear. We collected saliva to determine proinflammatory cytokine levels and used subgingival calculus and surrounding tissues from patients with periodontitis for oral microbiota analysis via 16s ribosomal RNA gene sequencing. THP-1 cells were stimulated with sterile-filtered saliva from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…At the same time, they also stimulate the host and activation of in ammatory cells and immune cells, which triggered systemic in ammation and immune response, leading to upregulation of in ammatory mediators' level and acute phase proteins level [12]. Il-6, IL-1β, and IL-8 were all in ammatory mediators that regulated the immune response in the host body to microbial infection and played a central role in the destruction of periodontal tissues [13][14][15]. In ammatory indicators such as IL-6, IL-1β, and IL-8 with an abnormal upward trend would aggravate the injury degree of vascular endothelial cells and further aggravate the in ammatory response of periodontal tissues, which may reduce the e ect of drug treatment and increase the risk of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they also stimulate the host and activation of in ammatory cells and immune cells, which triggered systemic in ammation and immune response, leading to upregulation of in ammatory mediators' level and acute phase proteins level [12]. Il-6, IL-1β, and IL-8 were all in ammatory mediators that regulated the immune response in the host body to microbial infection and played a central role in the destruction of periodontal tissues [13][14][15]. In ammatory indicators such as IL-6, IL-1β, and IL-8 with an abnormal upward trend would aggravate the injury degree of vascular endothelial cells and further aggravate the in ammatory response of periodontal tissues, which may reduce the e ect of drug treatment and increase the risk of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Facing the challenge from bacteria, inflammatory cytokines such as IL-1β, IL-6 and IL-8 will be released by periodontal tissue cells and immunocytes, and these cytokines play important roles in the process of tissue destruction ( Pan et al., 2019 ; Huang et al., 2021 ). The anti-inflammatory effect of Rd has been demonstrated in other inflammatory diseases ( Liu et al., 2018 ; Yang et al., 2020 ) but rarely discussed in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that TDGs contained Rutin, Caffeic acid, Cryptotanshinone, Tanshinone IIA, Formononetin, Liquiritin, Danshensu, and other active ingredients. Tanshinone IIA, Cryptotanshinone, and Danshensu are the three main bioactive components of Salvia miltiorrhiza Bunge, while all of them has proved to alleviate psoriasis [12,[20][21][22]. Formononetin proved to has strong anti-proliferation properties [23].…”
Section: Discussionmentioning
confidence: 99%